Find the concentration of radon gas emitted naturally from the bones and skin of some kinds of birds and local and imported chicken available in the City of Baghdad (Baghdad Science Journal, 2015)
In the present research we the study the deposition of radioactive elements naturally and particularly radioactive radon gas in parts of the body of organisms which are of direct relevance to human life in the city of Baghdad as the samples which were collected from the bones and skin of some kinds of birds and chicken based on the principle that radioactive elements are concentrated always on the bones. We use of this as the exercise detector impact nuclear (CR-39), using the technology Cylindrical diffusion , the results indicated that the largest concentration of radon found in the bone bird Seagull tapered as it was (625 ± 37) Bq.cm-3, and less concentration of radon gas in the chicken bones of Al-kafeel as it was (105 ± 10) Bq.cm-3 as well as in chicken bones of Al-muriad to be reached (110±10)Bq.cm-3 either in the skin reached the highest concentration in the skin of seagulls tapered(610 ± 20) Bq.cm-3 and the lowest value in the skin local chicken as it was (90 ± 9) Bq.cm-3 .